Development of health literacy assessment tool for 9-10 Years old children in Thailand - Nopparat Senahad; Wongsa Loahasiriwong; Sarawut Boonsuk (Elsevier, 2023)
Objectives: This study developed psychometric evaluation of an instrument for measuring health literacy among children in Thailand. Study design: Development of Health Literacy Assessment Tool for 9-10 Years Old Children in Thailand involved item development. The first step was reviewing literature to pilot-test and generate an item pool. Nine expertise with different disciplines were approached to assess the initial questionnaire. For field-testing, 1650 students with same age group were randomly selected to complete the questionnaire. The psychometric properties of the developed instrument were assessed by an Exploratory Factor Analysis (EFA) and a Confirmatory Factor Analysis (CFA). Results: A total of 50-items were included in exploratory factor analysis indicating 4-dimension solution that jointly explained 36.05% of the variance observed. Confirmatory factory analysis also indicated a good fit of the data for the four-latent structure: access to information (9-items), understanding the information (6-items), appraisal (8-items), and apply the information (9-items) (Chi-square: χ2 = 1530.76), (Goodness-of-Fit Index: GFI = 0.937), (Adjust GFI: AGFI = 0.927), (Standardized root mean-square residual: SRMR = 0.025); (Root mean-square error of Approximation: RMSEA = 0.040), (Comparative-fit-Index: CFI = 0.903) and (Normed-fit-index: NFI = 0.910). Additional analysis for internal consistency observed satisfactory results with overall Cronbach's alpha coefficient of 0.902. The Item-Total Correlation (ITC) was 0.300 (range:0.319 to 0.518) and high validation with value of CVI of 0.87. Conclusions: Health Literacy Assessment Tool for 9-10 Years Old children (31-item) showed psychometric properties, high validityy and was reliable. Therefore, it is considered as an effective tool to measure the Health Literacy for 9-10 years old children in Thailand.